Exploring Academic Satisfaction of Operating Room MSc Students at Medical sciences Universities in Iran During the Academic Year 2022-2023 - Hannani, Sedighe; Torkashvand, Zahra; Amiri, Fardin; Azadi, Nammam (Advances in Nursing & Midwifery, 2024)
Introduction: This study investigates the academic satisfaction of master’s level operating room students, who are potential future faculty members. This exploration aids in monitoring the educational system of medical sciences universities in Iran. Methods: This 2022 cross-sectional survey research included all 131 master’s students in operating room technology across Iran for the academic year 2022-2023. Students in Tehran completed the questionnaires in person, while those from other provinces responded electronically. Data were collected using a demographic profile form and a researcher-developed academic satisfaction questionnaire. The validity and reliability of the questionnaire were confirmed. Data analysis was performed using SPSS26 software. Results: Of the 131 students participating in the study, 72% were female, 65% were employed, 61% were married, and 26% were local residents. The overall academic satisfaction was average (with a mean score of 66 in a range of 23 to 115). Factors such as the host university, undergraduate GPA, academic semester, employment status, marital status, gender, and parents’ education significantly influenced academic satisfaction (P<0.05). Conclusions: The academic satisfaction of master’s level operating room students was moderate. To enhance student satisfaction, steps such as creating favorable conditions to advance the operating room field at the master’s level and providing specialized training for postgraduate specialists are necessary. Enhancing specialized skills can foster a more positive attitude among students towards their field of study, thereby increasing their academic satisfaction.